Applying Kotler’s 5A model to TikTok live: A systematic literature review - Gusty, Ryndian; Darniyus, Al-Adly (Priviet Social Sciences Journal, 2025)
Live streaming of TikTok is an important factor in digital marketing success, and its application remains questionable. Rapid development of the skincare industry has created a competitive promotional strategy. This study analyzes how TikTok life can increase skincare sales and the factors that can influence it. This study uses a systematic literature review (SLR) method to analyze the implementation of TikTok Live as a digital marketing strategy in the skincare industry. A total of 38 articles published between 2026 and 2025 were reviewed. The data were analyzed thematically using open and axial coding, structured according to Kotler's 5A framework, and supported by the stimulus-organism-response theory, consumer involvement theory, and technology acceptance models. The results show that TikTok Live has become a digital marketing strategy used to increase skincare sales. Awareness and Appeal have a broad impact and create audience interest through creative visual videos that interact directly with the audience. The ask stage is strengthened through direct consumer communication during live broadcasts through comments. In the Act stage, audiences quickly and easily conduct product transactions. Advocacy forms consumer loyalty to a skincare brand, because customers feel satisfied with the products used. This study provides new insights by combining direct marketing strategies with consumer behavior models. TikTok Live is not only a transactional medium but also a platform for consumer social and emotional engagement.